Vascularización coronaria de la tortuga marina Chelonia mydas - Quesada, Rafael; Madriz, Luis Fdo. (Revista de Biología Tropical, 1986)
The irrigation of the heart of the green turtle (Chelonia mydas) was studied through the clearing and disection techniques. Five coronary new irrigation patterns were found. The presence of anastomoses is discussed along with the number and position of the colateral vessels.